Global Database-Driven Assessment of HIV-1 Adaptation to the Immune Repertoires of Human Populations - Karakas, Aram (J Virol, 2015)
Associations between HIV-1 cytotoxic T lymphocyte (CTL) escape mutations and their restricting human leukocyte antigen (HLA) alleles imply that HIV could adapt to divergent HLA repertoires of human populations globally. Using publicly available databases, we examine the relationship between the frequencies of 19 experimentally validated CTL escape mutations in HIV-1 reverse transcriptase and their restricting HLA alleles in 59 countries. From these extensive data, we find evidence of differential HIV adaptations to human populations at only a limited number of the studied epitope sites.